Centralized care model for hereditary angioedema overcomes geographical barriers - Holmes, Ashley; Srinivasan, Cindy; Borle, Jack; Blain, Heather; Ritchie, Bruce; Adatia, Adil (Frontiers in Immunology, 2024)
Hereditary angioedema due to C1 inhibitor deficiency (HAE) is a rare inborn error of immunity that presents with episodic swelling. Management is multifaceted and includes on-demand treatment of swelling episodes, short-term prophylaxis to prevent swelling episodes from procedures, and longterm prophylaxis (LTP) to prevent angioedema on an ongoing basis. All approved on-demand therapies are parenteral, necessitating patient training for home administration, particularly intravenous C1 inhibitor. These complexities can result in care gaps for rural HAE patients. We conducted a cross-sectional study at our Angioedema Center of Reference and Excellence to assess the care provided to urban and rural patients. The proportion of patients receiving LTP, proportion of patients diagnosed as children, and disease control measured using the Angioedema Control Test (AECT) were collected. Logistic and Poisson regression models adjusted for age and sex were used to compare the two groups. The proportion using LTP was similar at 62% and 61% in urban and rural patients, respectively (odds ratio [OR] 1.01 (CI 95% 0.34-2.99)). Among urban patients, 52% were diagnosed as children compared to 60% among rural residents (1.43 (0.37-5.56)). The mean (IQR) AECT score was 14.0 (8.5-15.5) in urban patients and 13.0 (10.0-14.0) in rural patients (Poisson  -0.001 (-0.23-0.23). These data indicate that rural patients received similar high-quality care. We attribute these findings to the centralized care model employed in which HAE patients in the region are seen at a single comprehensive care clinic.